Once Again to the Subject of Economic Sociology - РадаевВадим Валерьевич (Journal of Economic Sociology, 2010)
The paper is devoted to the determination of the subject of economic sociology. The author analyzes the problem of the boundaries of economic theory and economic sociology. The basic foundations of economic sociology are disclosed in the paper. The author suggests the ways of constructing the models of economic-sociological man. The term of action strategy is defined and discussed.